The Importance Of The Successful Use Of Information Technology As A Tool For Improving Organizational Performance In The Bank Of Agriculture And Rural Development - Tchikou, Abdelkader; Bouklia, Mohamed (جامعة الوادي - University of Eloued, 2023)
This study aims to analyse the impact of implementing information and communication technology as an improvement tool for the organizational performance at the Bank of BADR. Where we developed a questionnaire related to the study variables, then this questionnaire was presented to the employees of the Bank of Agriculture and Rural Development (Algiers Down Town) and they recovered 82% of it. The results obtained showed that information and communication technology have significant positive effects between the level of using information and communication technology tools (networks, software and techniques), and organizational performance thus operational performance among the employees. Additionally, it highlights the importance of the successful using information and communication technology as a main requirement for Algerian banks, in order to improve the organizational performance, and thus achieving the highest degree of efficiency and effectiveness of performance.
مقال
Keywords: Information and communication technology (ICT) ; Organizational performance ; Bank of BADR